ANALISIS PENDAPATAN MASYARAKAT PENGRAJIN ANYAMAN BAMBU DI DESA ENGKAHAN KECAMATAN SEKAYAM KABUPATEN SANGGAU - Doni, Ewaldus; Hardiansyah, Gusti; Idham, M (JURNAL HUTAN LESTARI, 2018)
The use of bamboo for woven crafts by the community has been going on for a long time and passed down through generations. Bamboo handicraft products are used for household needs, and some woven bamboo handicrafts are sold to increase income. This is conducted as an effort to get added value while waiting for the harvest of agriculture. This study aims wereto calculate the income of bamboo woven craftsmen in Engkahan Village, and to calculate the effect of working hours (X) on the income of bamboo woven craftsmen (Y). The study was conducted for four weeks, starting on 14 May 2018 to 16 June 2018 in Engkahan Village. The research was conducted by survey method with direct interview technique using questionnaire. The results showed that there were three species of bamboo used by craftsmen as raw material for making crafts. The three species of bamboo are bamboo reed (Schizostachyum brachycladum kurz), betung bamboo (Dendrocalamus assper (Schult) Becker ex Heyne), and bamboo pisak (Schizostachyum lima (Blanco) Merril). The income earned by craftsmen from the business of making bamboo woven crafts was averaged of Rp. 1,395,340.91 per year. The lowest income earned by craftsmen is Rp. 725,000 per year, and the highest income earned by craftsmen is Rp. 2,625,000 per year. Data processing results showed that variable X (number of working hours) affects the variable Å¶ (craftsman income), with the form of the regression equation obtained as follows: Å¶ = 515.030.50 + 4,585.63 X. The equation illustrates that each additional hour of work by craftsmen will contribute Rp. 4,585.63 to the income of the bamboo woven craftsmen.Keywords:bamboo species, bamboo woven products,Â  craftsman income